2011
DOI: 10.4028/www.scientific.net/amm.110-116.4723
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Variation of Microstructural Parameters in Titanium Alloys during near Superplastic Regime of Deformation

Abstract: Deformation of Titanium alloys close to optimal superplastic condition i.e. near superplastic regime of deformation leads to significant change in microstructures.VT-9 titanium alloy was used in order to find out those parameters of microstructure which are varying significantly during near superplastic regime of deformation. Tensile tests were carried out at 930°C up to fracture with a constant strain rate of 5*10-4 s-1 and a jump wise varying strain rate of 1*10-4 s-1 & 5*10-4 s-1 .The microstructural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Because of its high hardness and wear resistance, Fe-Cr-C-Ti alloy has been widely applied in metallurgical, mineral and cement industries [1][2][3]. According to its microstructure, the Fe-Cr-C-Ti alloy can be divided into hypoeutectic, eutectic and hypereutectic ones, and the microstructure is mainly composed of martensite and complex carbides, such as MC, M 7 C 3 and M 23 C 6 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high hardness and wear resistance, Fe-Cr-C-Ti alloy has been widely applied in metallurgical, mineral and cement industries [1][2][3]. According to its microstructure, the Fe-Cr-C-Ti alloy can be divided into hypoeutectic, eutectic and hypereutectic ones, and the microstructure is mainly composed of martensite and complex carbides, such as MC, M 7 C 3 and M 23 C 6 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…9 In superplastic forming industry, deformation process is carried out not at optimal but closes to the boundary of optimal superplastic condition that is called near superplastic regimes for which microstructure changes significantly during the deformation process. 11 For computer simulation of these industrial processes, it is very much essential to develop a constitutive equation that can also take into account the major changes in microstructure that takes place during non-optimal process of superplastic deformation. It has already been reported that the average grain size of Ti-6Al-4V titanium alloy changed from its initial value during non-optimal regime of superplastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In real technological application, maintenance of these narrow ranges of condition required for optimal superplastic flow from beginning to end is a very difficult and challenging task 9. In superplastic forming industry, deformation process is carried out not at optimal but closes to the boundary of optimal superplastic condition that is called near superplastic regimes for which microstructure changes significantly during the deformation process 11. For computer simulation of these industrial processes, it is very much essential to develop a constitutive equation that can also take into account the major changes in microstructure that takes place during non-optimal process of superplastic deformation.…”
Section: Introductionmentioning
confidence: 99%